Protein synthesis and the cell cycle: centrosome reproduction in sea urchin eggs is not under translational control (The Rockefeller University Press, 1990)
The reproduction, or duplication, of the centrosome is an important event in a cell's preparation for mitosis. We sought to determine if centrosome reproduction is regulated by the synthesis and accumulation of cyclin proteins and/or the synthesis of centrosome-specific proteins at each cell cycle. We continuously treat sea urchin eggs, starting before fertilization, with a combination of emetine and anisomycin, drugs that have separate targets in the protein synthetic pathway. These drugs inhibit the postfertilization incorporation of [35S]methionine into precipitable material by 97.3-100%. Autoradiography of SDS-PAGE gels of drug-treated zygotes reveals that [35S]methionine incorporates exclusively into material that does not enter the gel and material that runs at the dye front; no other labeled bands are detected. Fertilization events and syngamy are normal in drug- treated zygotes, but the cell cycle arrests before first mitosis. The sperm aster doubles once in all zygotes to yield two asters. In a variable but significant percentage of zygotes, the asters continue to double. This continued doubling is slower than normal, asynchronous between zygotes, and sometimes asynchronous within individual zygotes. High voltage electron microscopy of serial semithick sections from drug- treated zygotes reveals that 90% of the daughter centrosomes contain two centrioles of normal appearance. From these results, we conclude that centrosome reproduction in sea urchin zygotes is not controlled by the accumulation of cyclin proteins or the synthesis of centrosome- specific proteins at each cell cycle. New centrosomes are assembled from preexisting pools of ready-to-use subunits. Furthermore, our results indicate that centrosomal and nuclear events are regulated by separate pathways.